Harlequin in Marketplace Culture - Pietropaolo, Domenico, (Brill Research Perspectives in Humanities and Social Sciences., 2025)
Since the late 19th century, the stock characters of the commedia dell'arte, especially Harlequin, Pulcinella and Pierrot, have been making frequent appearances in the world of material and cultural artifacts, in such categories as the entertainment industry, the food market, politics and education. This book explores the manner in which commedia dell'arte characters and narratives have been instrumentalized to serve commodity marketing, political critique, the arts and cultural pedagogy. Some embodiments of commedia dell'arte demonstrate an extraordinary capacity for serious reflection, reaching out, from within the heart of popular culture, to aesthetic ideals and cognitive depth of a remarkable degree.